RELATIONSHIP BETWEEN FUNCTIONAL FITNESS AND SELF-RATED HEALTH IN ELDERLY INVOLVED IN AN INTERVENTIONAL EXERCISE PROGRAM (Fiep Bulletin - online, 2011)
Physical activity is directly associated to an increased quality of life among elderly people by increasing their functional capacity and independence. OBJECTIVE: Thus, the aim of this study was to analyze the relationship between self-rated health (SRH) and functional capacity of the elderly. We hypothesized that subjects who obtained better results in functional tests tend to have a better SRH. METHODOLOGY: These are preliminary results of an interventional program developed in Maia/Portugal, comprised of 900 subjects, aimed to evaluate the effects of different training methodologies. Our sample consists of 167 subjects, aged 60 to 74. The functional capacity was measured by Rikli & Jones (1999) functional fitness battery. The SRH was evaluated by the international questionnaire Medical Outcome Study – 36 items from health survey- short version (SF-36). Statistical analysis was performed using SPSS (Windows version 17.0) and the level of significance was set up at p≤0.05. RESULTS: SRH was significantly associated with four different functional tests (p≤0.05). Subjects who belong to the 4th quartile in tests related to locomotion correspond to those subjects who had the best perception of health. CONCLUSION: We observed that SRH is associated to functional fitness, especially in those tests related to locomotion capacity.
Keywords: Perception of health; elderly; functional ability